2012
DOI: 10.1111/j.1600-6143.2012.04177.x
|View full text |Cite
|
Sign up to set email alerts
|

Risk of End-Stage Renal Disease Among Liver Transplant Recipients With Pretransplant Renal Dysfunction

Abstract: Guidelines recommend restricting simultaneous liverkidney (SLK) transplant to candidates with prolonged dialysis or estimated glomerular filtration rate (eGFR) <30 mL/min/1.73m 2 for 90 days. However, few studies exist to support the latter recommendation. Using Scientific Registry of Transplant Recipients and Medicare dialysis data, we assembled a cohort of 4997 liver transplant recipients from February 27, 2002-January 1, 2008. Serial eGFRs were calculated from serum creatinines submitted with MELD reports. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
67
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(69 citation statements)
references
References 22 publications
1
67
1
Order By: Relevance
“…5,15,18 Studies have shown that patients on the waiting list with a high MELD score can develop pretransplant renal dysfunction, which increases the risk of renal failure after transplant. [19][20][21] In addition, a correlation was noted between high PELD/MELD score and increased length of posttransplant hospitalization. 18,[22][23][24][25] Our experience was similar to the results reported in the literature.…”
Section: Discussionmentioning
confidence: 96%
“…5,15,18 Studies have shown that patients on the waiting list with a high MELD score can develop pretransplant renal dysfunction, which increases the risk of renal failure after transplant. [19][20][21] In addition, a correlation was noted between high PELD/MELD score and increased length of posttransplant hospitalization. 18,[22][23][24][25] Our experience was similar to the results reported in the literature.…”
Section: Discussionmentioning
confidence: 96%
“…Those covariates with P#0.05 were included in the final model. The following baseline covariates determined at the time of LTwere included in model selection based on these data and previous studies: 2,5,18,19 recipient age, sex, race, diagnosis, BMI, status-1 (acute liver failure), pre-LT hypertension, diabetes mellitus, hospitalization status at LT, on life support at LT, on RRT at LT, previous LT, history of TIPSS, serum bilirubin, serum creatinine, slope of creatinine, acute dialysis, INR, serum sodium, and serum albumin.…”
Section: Model Buildingmentioning
confidence: 99%
“…Serum creatinine is a poor marker for renal dysfunction in the liver disease population and tends to overestimate renal function (12). The existing literature (6) suggests that patients with CKD and low GFR require combined liver-kidney transplantation. The definition of CKD chosen was formulated by incorporating the current published literature with the observed characteristic of SLK patients discussed above.…”
Section: Medical Eligibility Criteriamentioning
confidence: 99%